2020
DOI: 10.1080/03091902.2020.1825847
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost biofuel-powered autoclaving machine for use in rural health care centres

Abstract: Surgical site infections (SSIs) in developing countries have been linked to inadequate availability of sterilising equipment. Existing autoclaves are mostly unaffordable by rural healthcare practitioners, and when they managed to procure them, the electricity supply to power the autoclaves is epileptic. The solar-powered autoclave alternatives are too bulky with a very high initial cost. Hence, low-cost biofuel-powered autoclave becomes an attractive option, and this study sought to present the design, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In addition, the issue of cost is magnified when considering the initial and operational cost of device reprocessing. For example, the initial cost of an affordable autoclave designed for LRS can be approximately US$ 85–620 or more ( 98 , 99 ) and possess an operational cost of US$ 50 per hour ( 100 ). Similarly, estimates suggest that one cycle of chemical sterilisation can cost US$ 5–10 ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the issue of cost is magnified when considering the initial and operational cost of device reprocessing. For example, the initial cost of an affordable autoclave designed for LRS can be approximately US$ 85–620 or more ( 98 , 99 ) and possess an operational cost of US$ 50 per hour ( 100 ). Similarly, estimates suggest that one cycle of chemical sterilisation can cost US$ 5–10 ( 101 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Arduino UNO (Arduino, Scarmagno, Italy) is the main part of the circuit of the system as all other components include resistor, buzzer, and others (Figure 4). Table 1 presents the justification for material selection in this study [22].…”
Section: Methodsmentioning
confidence: 99%
“…Currently, 930 million people globally face medical expenses equalling 10% of their household income [26]. A survey of 50 sub-Saharan countries reported that currently there are 98,745 health care centres [27]. Solar energy is the only renewable energy source that can provide a truly zero carbon energy source for use in remote health care centres catering to millions.…”
Section: Introductionmentioning
confidence: 99%